PELAYANAN HAJI KHUSUS PIHK AZIZI KENCANA WISATA KOTA MEDAN - M. Agus Noorbani (Jurnal Dialog, 2016)
Hajj service management is one of the main responsibilities of Ministry of Religious Affairs (MoRA). Besides MoRA, the Law No. 13 Year 2008 on the management of Hajj also mentions that public institutions can be involved in hajj management service ]which includes Special Hajj Service (PIHK). This research is a case study to investigate the management of Special Hajj Service by PIHK Azizi Kencana Wisata in Medan. This study found out that there were some repetitive violations on the Special Hajj service in Medan. These violations might be caused by the insufficient monitoring by the local office of Ministry of Religious Affairs that does not have authority to conduct monitoring and to give penalties to Hajj service providers who commit violations. KEY WORDS: Special hajj, PIHK, public service, Medan